Caracterização fenotípica e molecular de feijoeiro-comum quanto à resistência à antracnose e estudo de herança - Ariadna Faria Vieira (2015)
The common bean (Phaseolus vulgaris L.) is one of the most important vegetables species worldwide, but the large number of diseases is one of the factors that undermine productivity, being the anthracnose (Colletotrichum lindemuthianum) one of the major fungal diseases related to bean crop. The wide variability of the pathogen is a challenge for the development of cultivars with broad-spectrum resistance. For this, it is necessary to identify, characterize and use of different fundamental sources of resistance to the success of breeding programs. Thus, the objectives of the two trials of this study were: (i) to characterize the phenotypic and molecular profile lines and common bean cultivars for resistance to anthracnose and, (ii) to study the inheritance of this trait in the cultivar 'BRS Cometa'. The experiments were conducted at the Centro Nacional Pesquisa em Arroz e Feijão, da Empresa Brasileira de Pesquisa e Agropecuária (CNPAF-EMBRAPA) in Santo Antônio de Goiás - GO. For the first experiment, they were conducted field testing and molecular characterization. For the field trial, 55 genotypes were planted in three installments of 3 meters long and spaced 0.5 meters apart. Genotypes were inoculated simultaneously with the races 65 (isolated Cl 1614); 73 (isolated Cl 1143); 81 (isolated Cl 1164); 91 (isolated Cl 1247); 475 (isolated Cl 1322) 1609 (isolate Cl 1294), with a final concentration of 1,2 x 106 spores/ml. The marks awarded to each genotype were given according to the percentage of leaves and/or plants. For the molecular characterization, 15 seeds of each of the 55 genotypes used were sown in pots in the greenhouse. At seven days after germination, leaf discs ten seedlings were collected in bulk for DNA extraction. Amplification reactions were performed with the SCAR markers previously identified as linked to anthracnose resistance genes Co-34 (SF10), Co-4 (SY20), Co-42 (SH18 and SAS13), Co-5 (SAB3) and Co-6 (SAZ20). For the second experiment, there was the inheritance study for resistance to C. lindemuthianum using the pathotype 91, isolated Cl 1247, the BRS Cometa. Families seeds F2:3, from the cross Rosinha G2 x BRS Cometa, in addition to parents and witness SEL 1308 (Co-42), were pre-germinated and planted in trays in a greenhouse. After seven days, individual plants were inoculated with a spore suspension with a concentration of 1,2 x 106 spores / ml. For assessments of disease severity, we used a grading scale ranging from 1 to 9. The observed phenotype frequencies (resistance: susceptibility) in the populations were tested using the chi-square test (2). As a result of the first experiment, 26 genotypes were resistant to the pathotypes 65, 73, 81, 91, 475 and 1609 of C. lindemuthianum and ten of these genotypes were considered immune. Only the marker SF10 (Co-34) was specific, to amplify other known resistance, such as K23 (Co-5), Kaboon (Co-12), Perry Marrow (Co-13), Cornell 49-242 (Co- 2), Mexico-222 (Co-3), SEL 1360 (Co-52), H1 (Co-7) and BRS Pitanga (Co-14). The SH18 marker was even allele-specific, discriminating Co-42 of Co-4. Analyzing the marker SF10, 31 genotypes amplified brand, representing 53.44% of total samples. The K10 strain showed the molecular markers SY20, SAB3 and SAZ20, indicating the presence of the Co-4 genes Co-5 and Co-6, respectively. The results of the second experiment showed that the segregation ratio for the resistance to the anthracnose F2: 3 families (Rosinha G2 x BRS Cometa) set is directed to the expected ratio of 1: 2: 1 (RR:Rr:rr) value of chi-square and 0.5 probability of 77.88%. This result indicates the presence of a single dominant gene involving resistance to pathotype 91 C. lindemuthianum the cultivar 'BRS Cometa'